Study of Fungal Contamination of Some Medicinal Plants and Food Covered For Mosul - Mohammed, Mishaal Ali; Al-Tamer, Maryam Yassar (American Journal of Biology and Natural Sciences, 2025)
The most isolated fungi from juices, meat, pears, rice, legumes, medicinal plants, spaghetti, pasta, anddomy, pistachios, currants and almonds collected from local markets in Mosul were the most isolated fungi from juices: yeasts and Penicillium spp fungus (25%) in both Saudi Captain juice and Jordan's Rowan. In Moroccan tank juices, Penicillium sp fungus were isolated by 12.5%, penicillium roqueforti fungus were isolated from Turkish Levance juice by 12.5%, while Yemeni-made quality juice, Kuwaiti Dalia juice and Jordanian Zaki juice were isolated. No type of fungus was isolated from it and the fungus was isolated from some types of frozen red and white meat and the results showed that both yeasts and Penicillium sp. fungus are the most isolated fungi, they were isolated by 33.33% of Turkish chicken meat, Penicillium spp fungus were isolated from fish meat by 16.66 percent, cladosporium spp fungi were isolated by 16.66 percent of roast meat, while the rest of the meat (Saudi kebabs, sausages and humberkers) were not isolated from them., while Aspergillus spp fungus were isolated by (33) 33% of the spaghetti is Turkish-made, but pasta has not isolated any type of fungi, and from the isolation of fungi from pistachios, currants and almonds, the results showed that the highest isolation rate was for both yeasts and afan, which amounted to (50%) in pistachios. Internal and currants, The isolation of fungi from rice and some legumes has shown the results to be the highest insulation rate for both A.niger fungi, Penicillium sp. Fusarium sp., Bacillus sp. reached (100%) of rice, chickpeas Rhizopus spp, Fusarium spp. and A.niger were isolated by 75%), Rhizopus sp mushrooms were isolated from lentils by (25%), beans were isolated from yeasts, advan and A.niger mushrooms by (75%),Fungi have been isolated from some types of medicinal plants all showed different types of isolated fungi, where both rhizopus sp mushrooms and Penicillium sp. A.niger has the highest isolation rate (18.75%) in corn, thyme and mirmian sycathing, fungi have been isolated by (12.5%) in other plants. In chamomile A.niger and Gliocladium spp were isolated. In the pond grain, Mucor spp and A.niger mushrooms were isolated and A.niger sheep were isolated from saffron, and isolated Yeasts and coriander abscesses Rhizopus spp and Fusarium spp were isolated from tea, while the lowest isolation rate was (5.88%) where Rhizopus spp fungi were isolated from the ring. Mucor spp were isolated from the strong and mountain mint, while in the Marmki plant, penicillium spp fungi were isolated.